IMPLEMENTASI NILAI-NILAI FILOSOFIS JOGED MATARAM KE DALAM SISTEM PEMBELAJARAN TARI SLTP KOTA YOGYAKARTA - Kuswarsantyo - (FBS UNY, 2007)
Various studies on the philosophical values of Joged Mataram have been conducted. However, in the context of dance learning, a study that relates the values and the dance learning system has never been carried out. Therefore, the writer is interested to analyze the problem through a descriptive qualitative research. The result and the effectiveness of the application of Joged Mataram philosophy to the dance learning system can be used as an achievement measurement, with dance teachers as the main informants. Four aspects of Joged Mataram philosophy are Sawiji, the realization of always concentrating on facing all activities; Greged, the expression of human life dynamic; Sengguh, human self-evidence in all situations without being arrogant; and Ora Mingkuh, an attitude of always struggling to realize a dream. Understanding the aspects, students are hopefully able to follow the dance learning process with all their heart to reach their ideals. Key Words: values, Joged Mataram, dance learning